Preventing Drug Abuse Among Hispanic Adolescents: Developing a Responsive Intervention Approach - Schinke, Steven P. (Res Soc Work Pract, 2014)
Intervention research is essential to help Hispanic American adolescents avoid drug use. This article describes an intervention research program aimed at preventing drug use among these youths. Grounded in salient epidemiological data, the program is informed by bicultural competence, social learning, and motivational interviewing theories. The program, called Vamos, is aimed at the risk and protective factors as well as the cultural prerogatives that demark the adolescent years of Hispanic American youths. Innovative in its approach, the program is delivered through a smartphone application (app). By interacting with engaging content presented via the app, youths can acquire the cognitive–behavioral skills necessary to avoid risky situations, urges, and pressures associated with early drug use. The intervention development process is presented in detail, and an evaluation plan to determine the program's efficacy is outlined. Lessons for practice and intervention programming are discussed.